DOP25 Association of Enterobacteriaceae with Crohn's Disease subtypes during remission. (27th May 2021) - Pisani, A; Rausch, P; Ellul, S; Bang, C; Tabone, T; Marantidis Cordina, C; Zahra, G; Ellul, P; Franke, A
Abstract: Background: Members of the Enterobacteriaceae have been associated with active Crohn's Disease (CD), possibly as a result of intestinal inflammation via production of a lipopolysaccharide that can trigger TLR4 signalling. This study aims to assess whether this association persists in remission of CD patients and whether correlation with disease phenotype is present. Methods: Stool samples of 32 CD patients in remission and 97 healthy controls were analyzed by 16S rRNA sequencing. High quality Amplicon sequence variants (ASV) were derived and classified via DADA2. Results: ASV 6- Escherichia/Shigella uncl . was found to be more abundant in CD (padj=0.0003) while ASV 24, another member of the Escherichia/Shigella cluster was identified as being an indicator species for CD (padj=0.09). Differential abundance analysis according to phenotype as per Montreal classification revealed that, compared to patients with the B1 phenotype, patients with the B2 and/or B3 have a higher abundance of Escherichia/Shigella uncl. (ASVs 13, 31, 282 and 422), Klebsiella uncl. (ASVs 75 and 101) and Enterobacter uncl. (ASV 219) (Figure 1). Furthermore, patients with L3 involvement had higher abundances of Klebsiella uncl . (ASVs 75 and 101) and Parasutturella uncl. (ASVs 22, 53, 120, 199, 249 and 510), the latter being a Proteobacteria, compared to patients with L1 and/or L2 involvement. No significant association with "Age of Onset" was identified. In addition, network analyses revealed a strongly correlated group of Enterobacteriaceae ASVs ( Klebsiella, Escherichia/Shigella, Enterobacter, Citrobacter ) which appear to collectively associate to CD. Abstract DOP25 – Figure 1: Heatmap visualizing significant differentially abundant ASVs in CD patients with respect to behaviour subgroups Conclusion: Enterobacteriaceae persist in the faecal microbiota in significantly higher levels than controls despite remission and furthermore are associated with the more severe phenotypes of stricturing and penetrating disease. Further studies might indicate whether microbiota assessment on diagnosis might predict CD subtypes and therefore influence therapeutic choices.